TEACHING ENGLISH AS A SECOND LANGUAGE (ESL) OR AS A FOREIGN LANGUAGE (EFL) (Modern education and development, 2025)
This article explores the intersection of theory and practice in the realm of teaching English as a second language (ESL). Drawing upon both pedagogical theories and practical classroom experiences, it examines the challenges faced by ESL educators and offers insights into effective teaching methodologies. The discussion encompasses topics such as language acquisition theories, cultural considerations, communicative approaches, technology integration, and assessment strategies. By synthesizing theoretical frameworks with real-world applications, this article provides valuable guidance for ESL instructors striving to enhance their teaching practices and promote language proficiency among learners.В данной статье исследуется пересечение теории и практики в сфере преподавания английского как второго языка (ESL). Опираясь как на педагогические теории, так и на практический опыт работы в классе, он рассматривает проблемы, с которыми сталкиваются преподаватели ESL, и предлагает понимание эффективных методологий преподавания. Обсуждение охватывает такие темы, как теории овладения языком, культурные аспекты, коммуникативные подходы, интеграция технологий и стратегии оценки. Путем синтеза теоретических основ с практическими приложениями эта статья предоставляет ценные рекомендации для преподавателей ESL, стремящихся улучшить свою педагогическую практику и повысить уровень владения языком среди учащихся.Uzbek Dieser Artikel untersucht die Schnittstelle von Theorie und Praxis im Bereich des Englischunterrichts als Zweitsprache (ESL). Es stützt sich sowohl auf pädagogische Theorien als auch auf praktische Unterrichtserfahrungen, untersucht die Herausforderungen, mit denen ESL-Pädagogen konfrontiert sind, und bietet Einblicke in effektive Lehrmethoden. Die Diskussion umfasst Themen wie Spracherwerbstheorien, kulturelle Überlegungen, kommunikative Ansätze, Technologieintegration und Bewertungsstrategien. Durch die Synthese theoretischer Rahmenbedingungen mit realen Anwendungen bietet dieser Artikel wertvolle Hinweise für ESL-Lehrer, die ihre Unterrichtspraktiken verbessern und die Sprachkenntnisse der Lernenden fördern möchten. Schlüsselwörter: TEFL, TESL, TEIL, sozialkonstruktivistische Pädagogik, kritische Pädagogik.